Sistem Monitoring Penentuan Pergerakan Posisi Panel Surya Terintegrasi Internet Of Things - Abdullah S; Moh. Zainul Haq (Politeknik Caltex Riau, 2021)
Due to the increasing demand for energy, alternative energy is needed. One of them is energy that comes from the sun. To utilize solar energy, solar panels are needed which are used to collect solar energy which will be converted into electrical energy. The problem is to optimize the work of the solar panel, a design for determining the position of the solar panel must be made so that it is always focused on the direction of the arrival of the sun. Design of solar panel position monitoring system based on the Internet of Things has a purpose as a monitoring system in optimizing the light reception received by solar panels in real time. The method used is the dual axis tracking method, which is a method that can make flexible solar panel movements follow the direction of the maximum sunlight intensity. The parameters monitored from this research are the value of analog voltage from the four LDR light sensors, two angles of dual axis movement and description of the the solar panel position. From the tests that have been carried out, the system can work well as solar panel movement position monitoring system based on the Internet of Things.